Microstructure-sensitive fatigue modelling of medical-grade fine wire - Clark, B. C.; Castelluccio, Gustavo M.; Reiterer, M. W.; McDowell, D. L.; Neu, R. W. (Wiley, 2018)
This work presents a modelling methodology to assess the sensitivity to microstructure in high‐cycle fatigue performance of fine wires made from MP35N alloy (35Ni‐35Co‐20Cr‐10Mo in wt%) used as conductors in cardiac leads. The model consists of a microstructure generator that creates a mesh of a statistically representative microstructure, a finite element analysis using a crystal plasticity constitutive model to determine the local response behaviour of the microstructure, and a postprocesser using fatigue indicating parameters to assess the likelihood of fatigue crack initiation. The fatigue crack initiation potency for selected microstructure attributes, boundary and interface conditions, and loading profiles is determined by computing the Fatemi‐Socie fatigue indicating parameter over a physically relevant volume of scale. Case studies are used to investigate (1) the influence of nonmetallic inclusion proximity to the wire surface on fatigue potency and (2) the transition life demarcating lives primarily controlled by fatigue crack initiation versus microcrack fatigue growth.
Keywords: Crystal plasticity; Fatigue indicator parameters; Fine wire; Inclusions